2021
DOI: 10.1002/anie.202101639
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Hot Carriers in Plasmonic Catalysis of C−N Bond Forming Reaction of Amines

Abstract: Here, we demonstrate the simultaneous utilization of both the hot carriers (electrons and holes) in the photocatalytic transformation of benzylamine to N‐benzylidenebenzylamine and the scope of reaction has also been successfully demonstrated with catalytic oxidation of 4‐methoxybenzylamine. The wavelength‐dependent excitation of AuNP allows us to tune the potential energy of charge carriers relative to the redox potential of the reactants which leads to energetically favorable product formation on the nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 65 publications
1
52
0
Order By: Relevance
“…The temperature increase for the AuÀ Pt NCs system due to light irradiation was estimated to be a few μK (see section S5c of supporting information), which is in line with the other literature reports. [3,56] This order of temperature increase cannot explain the observed trend. Moreover, our wavelength-dependent study clearly shows that the reaction is mostly charge carrierdriven and not photothermal driven.…”
Section: Proposed Mechanism For the Cascade Reduction Reactionmentioning
confidence: 84%
“…The temperature increase for the AuÀ Pt NCs system due to light irradiation was estimated to be a few μK (see section S5c of supporting information), which is in line with the other literature reports. [3,56] This order of temperature increase cannot explain the observed trend. Moreover, our wavelength-dependent study clearly shows that the reaction is mostly charge carrierdriven and not photothermal driven.…”
Section: Proposed Mechanism For the Cascade Reduction Reactionmentioning
confidence: 84%
“…In a recent study by Chandra and co‐workers, a simultaneous utilization of both hot electrons and hot holes in photoexcited AuNPs was achieved for the CN bond formation, by the oxidative amine coupling without the use of any hole/electron scavenger or support. [ 132 ] The authors reported for the first time the use of AuNP as both the light absorber as well as the catalyst to drive oxidative coupling of amine to imine at ambient conditions. The reaction was carried out using AuNPs as the sole plasmonic photocatalyst with benzylamine as the hot hole acceptor and atmospheric O 2 as the hot electron acceptor, under visible light excitation (Figure 8c).…”
Section: Hot Charge Carrier Driven Plasmonic Photocatalysismentioning
confidence: 99%
“…In such conditions, the reaction rate will be proportional to the scavenging power of sacrificial agents, which essentially depends on the difference between the energy levels of the sacrificial agent and the plasmonic photocatalyst: higher the difference, higher the scavenging power, and thus higher the reaction rate. [ 38,132,173 ] Figure 10c shows the energy levels of commonly used hole scavengers in photocatalysis, with respect to the Fermi energy of AuNPs. As can be seen from the energy level diagram, alcohols have higher oxidation potential than water, which means the former is a better hole scavenger.…”
Section: Hot Charge Carrier Driven Plasmonic Photocatalysismentioning
confidence: 99%
See 2 more Smart Citations